PENGENALAN SENI BELA DIRI PADAANAK-ANAK DANREMAJA DESA UNTUK MENAMBAH AKTIVITAS POSITIF PADA MASYARAKAT - Firdaus Firdaus (UII, 2013)
Cancer of the cervix or also called cervical cancer is a type of cancer that 99.7%are caused by human papilloma virus (HPV) oncogenic, which attacks the cervix. Riskgroup for the occurrence of cervical cancer arewomen over age 30 years who havemany children and to maintain reproductive health behavior is still lacking. Habitsmutually exchange sexual partners is one of the main factors of HPV virus that causescervical cancer is the case. In Indonesia only 5 percent who do cervical cancer screening,so that 76.6 percent of patients as detected has entered Stage Advanced (IIIB above),since cervical cancer usually without any symptoms in the initial stage. This fact isgenerally not known by the villagers. Therefore for prevention will be held related toreproductive health counseling and knowledge about menstruation on the PKK in thevillage of Wonogiri, Tawangsari, Kaligesing, Central Java.